PREDICTING CONTINUED USAGE INTENTION BASED ON FIT CONFIDENCE, INNOVATINESS, IMMERSION, AND USER PERCEIVED VALUES - William; Sabrina Sihombing (Universitas Pelita Harapan, 2026)
This study aims to analyze the influence of fit confidence, innovativeness, and immersion on continued usage intention through perceived hedonic value, utilitarian value, and social value. The research approach employed a quantitative method with a survey method of AR-based application users, with a purposive sampling technique to ensure respondents were relevant users. Data analysis was conducted using Structural Equation Modeling (SEM) to test the direct and indirect relationships between variables. The results showed that not all proposed hypotheses were empirically proven; however, several variables such as immersion and social value were shown to have a significant influence on continued usage intention. These findings confirm that the level of user engagement and perceived social value are important factors in driving continued usage intention towards AR technology. This study provides theoretical contributions to the digital marketing literature as well as practical implications for developers and marketers in designing engaging and valuable user experiences.